Does marriage protect mental health? Evidence from the COVID‐19 pandemic. (7th September 2021) - Jace, Clara E.; Makridis, Christos A.
Abstract: Using weekly variation from April 23 to June 23 2020, we exploit the surge in unemployment over the coronavirus pandemic to identify the effects on mental health outcomes and the role of marital status as a protective factor for households. We find that married respondents are 1–2 percentage points less likely, relative to their unmarried counterparts, to experience mental health problems following declines in work‐related income since the start of the pandemic. Our results suggest that the combination of intrafamily substitution and the psychological benefits of marriage helps insure against unanticipated fluctuations in job and income loss.